High-Voltage Test and Measuring Techniques - Hauschild, Wolfgang; Lemke, Eberhard (Springer International Publishing : Imprint: Springer, 2019)
The new edition of this book incorporates the recent remarkable changes in electric power generation, transmission and distribution. The consequences of the latest development to High Voltage (HV) test and measuring techniques result in new chapters on Partial Discharge measurements, Measurements of Dielectric Properties, and some new thoughts on the Shannon Theorem and Impuls current measurements. This standard reference of the international high-voltage community combines high voltage engineering with HV testing techniques and HV measuring methods. Based on long-term experience gained by the authors the book reflects the state of the art as well as the future trends in testing and diagnostics of HV equipment. It ensures a reliable generation, transmission and distribution of electrical energy. The book is intended not only for experts but also for students in electrical engineering and high-voltage engineering.